Differential hepatoprotective role of the cannabinoid CB1 and CB2 receptors in paracetamol-induced liver injury - Rivera-González, Patricia; Vargas, Antonio; Pastor, Antoni; Boronat, Ana; Lopez-Gambero, Antonio Jesus; Sanchez-Marin, Laura; Medina-Vera, Dina; Serrano, Antonia; Pavón, Francisco javier; De la Torre, Rafael; Agirregoitia, Ekaitz; Lucena-González, María Isabel; et al. (British Pharmacological Society, 2020)
Background and purpose: Protective mechanisms of the endogenous cannabinoid system against drug-induced liver injury (DILI) are actively being investigated regarding the differential regulatory role of the cannabinoid CB1 and CB2 receptors in liver fibrogenesis and inflammation. Experimental approach: The 2-arachidonoylglycerol (2-AG)-related signalling receptors and enzymatic machinery, and inflammatory/fibrogenic factors were investigated in the liver of a mouse model of hepatotoxicity induced by acute and repeated overdoses (750 mg·kg-1 ·day-1 ) of paracetamol (acetaminophen), previously treated with selective CB1 (ACEA) and CB2 (JWH015) agonists (10 mg·kg-1 ), or lacking CB1 and CB2 receptors. Key results: Acute paracetamol increased the expression of CB2 , ABHD6 and COX-2, while repeated paracetamol increased that of CB1 and COX-2 and decreased that of DAGLβ. Both acute paracetamol and repeated paracetamol decreased the liver content of acylglycerols (2-AG, 2-LG and 2-OG). Human liver samples from a patient suffering APAP hepatotoxicity confirmed CB1 and CB2 increments. Acute paracetamol-exposed CB2 KO mice had higher expression of the fibrogenic αSMA and the cytokine IL-6 and lower apoptotic cleaved caspase 3. CB1 deficiency enhanced the repeated APAP-induced increases in αSMA and cleaved caspase 3 and blocked those of CYP2E1, TNF-α, the chemokine CCL2 and the circulating γ-glutamyltransferase (γGT). Although JWH015 reduced the expression of αSMA and TNF-α in acute paracetamol, ACEA increased the expression of cleaved caspase 3 and CCL2 in repeated paracetamol. Conclusion and implications: The differential role of CB1 versus CB2 receptors on inflammatory/fibrogenic factors related to paracetamol-induced hepatotoxicity should be considered for designing alternative therapies against DILI.
Keywords: Paracetamol; Liver injury; Cannabinoids